Turnover Intention and Its Associated Factors Among Psychiatrists in 41 Tertiary Hospitals in China During the COVID-19 Pandemic - Yang, Yating; Zhang, Ling; Li, Mengdie; Wu, Xiaodong; Xia, Lei; Liu, Daphne Y.; Liu, Tingfang; Liu, Yuanli; Jiang, Feng; Tang, Yi-lang; Liu, Huanzhong; Kalow, Nadine J. (Frontiers in Psychology, 2022)
Background: Turnover intention, an employee's intention to voluntarily leave their jobs, affects workforce sustainability. However, scarce data are available about the turnover intention and its associated factors among psychiatrists in China, especially during the COVID-19 pandemic. The current research was designed to address this gap. Methods: An anonymous, nationwide online survey was disseminated to psychiatrists in 41 psychiatric hospitals in China. We collected demographic data, job-related information (duration of employment, history of participation in the front-line work against COVID-19, job satisfaction), and participants’ turnover intention in the next 12 months. Results: In total, 3,973 psychiatrists completed the survey. The sample was predominantly female (58.8%), married (79.5%), and nealry three fourths (73.5%) had children. More than one-third (35.6%) had a master’s or doctoral degree in addition to their medical degree. The overall level of job satisfaction was moderate. The rate of turnover intention was 22.0% (22.9% in males and 21.3% in females, respectively). Psychiatrists who had participated in the front-line work of COVID-19 were more likely to report an intention to leave their current job. Multiple regression analyses suggested that turnover intention was significantly associated with having insomnia, longer working hours, and more working days per week. Conclusion: During the pandemic period, approximately one-fifth of psychiatrists in China reported turnover intention. Factors associated with turnover intention included high job-related burdens, low job satisfaction, participation in the front-line work against COVID-19, and insomnia. To improve psychiatric workforce sustainability, policymakers and hospital administrators need to be aware of this potential challenge and address the concerns of psychiatrists in China.